IMPACT OF SUB-SOILING, LAND CONFIGURATION AND ZINC FERTILIZATION ON GROWTH, YIELD AND QUALITY OF CASTOR (RICINUS COMMUNIS L.) - MATHUKIA, R.K.; KHANPARA, V.D. (Annals of Agricultural Research, 2014)
The experiment Â during kharif 2003 at Junagadh Agricultural University, Junagadh to ascertain the effect of sub-soiling, land configuration and zinc fertilization on growth, yield and quality of castor (Ricinus communis L.). Various moisture conservation practices significantly influenced growth, yield and quality characters as well as seed and stalk yields. Various moisture conservation practices significantly influenced growth, yield and quality characters as well as seed and stalk yieldsyield over control (Z1), while zinc levels couldnot cause their significance impact on number ofinternodes and spikes/plant